Situation Report: Hungary, 11 May 1979 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Tihany Ideological Conference: Conflict at a Low Level? A Democratic or a Liberal Alternative to Centralized Bureaucracy What Is the "Right" Size for an Enterprise? "Evening" Craftsmen to Supplement Artisans' Services Gaspar Speaks on International Trade Union Co-Operation The Interdependence of Politics and Science Enhanced New Opportunities for Increasing Independence of Agricultural Co-Operatives